Divergence of West African and North American communities of Aspergillus section flavi - Cotty, P.J.; Cardwell, K.F. (1999)
West African Aspergillus flavus S isolates differed from North American isolates. Both produced aflatoxin B1. However, 40 and 100% of West African isolates also produced aflatoxin G1 in NH4 medium and urea medium, respectively. No North American S strain isolate produced aflatoxin G1. This geographical and physiological divergence may influence aflatoxin management.